Poverty Data Revolution: Analyzing The Effectiveness Of Damsida Application in Bojonegoro District - Cahya Lukito; Esa Septian; Lucky Luklui Najah; Muhammad Syahrul Muhromi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The DAMISDA application was developed by the Bojonegoro Regency Government to address data accuracy challenges in poverty alleviation, aiming to facilitate effective social assistance targeting. This study examines DAMISDA's effectiveness through three primary indicators: goal achievement, integration, and adaptation. A descriptive qualitative approach was employed, incorporating in-depth interviews, observations, and document analysis to assess the application’s performance. Findings indicate that DAMISDA has enhanced poverty data accuracy, aiding precise targeting in social assistance distribution. However, issues such as inclusion errors and network instability hinder optimal efficiency, affecting data updates and timely interventions. The integration process is supported by clear procedures and extensive socialization efforts, though network limitations impact seamless implementation. Adaptation efforts, including operator training, have improved application usage, but technological infrastructure constraints remain a significant challenge. The study underscores DAMISDA's potential as a model for data-driven poverty interventions, suggesting policy improvements in infrastructure and validation processes. This research contributes to e-government literature by highlighting the role of digital tools in poverty management, particularly in rural Indonesia. Further exploration is recommended to evaluate DAMISDA’s adaptability in broader contexts, contributing to more resilient and accessible digital platforms for targeted poverty alleviation.